Income Diversification and Financial Sustainability of Microfinance Institutions In Kenya - Talel, Livingstone Cheboi; Asienga, Irene; Githaiga, Peter Nderitu (The Journal of Financial, Accounting, and Economics, 2024)
The purpose of this paper was to investigate the effect of income diversification and financial sustainability of microfinance institutions in Kenya. The study used panel data drawn from 32 MFIs over the period 2010-2019 that yielded 320 observations. The data was sourced from the MIX market, a World Bank Database for all MFIs that self-report. Data was analyzed through the ordinary least squares (OLS), the system generalized method of moments, the fixed effect and random effect model. The findings revealed that income diversification had a positive significant relationship to the sustainability of microfinance institutions in Kenya. The results further revealed that breadth of outreach, firm size, average loan size, debt to equity ratio and portfolio at risk (Par>30) had a significant effect on financial sustainability of microfinance institutions in Kenya. Based on the findings this study recommend that MFIs should consider income diversification in their effort towards attaining financial sustainability